2016
DOI: 10.1128/mbio.01261-16
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Erythrocyte Binding Protein of Plasmodium vivax Suggests an Alternate Invasion Pathway into Duffy-Positive Reticulocytes

Abstract: Erythrocyte invasion by malaria parasites is essential for blood-stage development and an important determinant of host range. In Plasmodium vivax, the interaction between the Duffy binding protein (DBP) and its cognate receptor, the Duffy antigen receptor for chemokines (DARC), on human erythrocytes is central to blood-stage infection. Contrary to this established pathway of invasion, there is growing evidence of P. vivax infections occurring in Duffy blood group-negative individuals, suggesting that the para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 30 publications
5
74
0
5
Order By: Relevance
“…When Pv RON4 binding to RBC ( m = 34 ± 2.7) was compared with binding to normocytes ( m = 11 ± 1.4), it was observed that the amount of rosettes compared with normocytes became significantly reduced, t test: t (10) = 18.68, p = .001 (Figure b,c). This suggested that Pv RON4 binding to RBC depends on a more immature RBC population, similar to that reported for other P. vivax antigens, such as Pv AMA1 (Arevalo‐Pinzon, Bermudez, Hernandez, Curtidor, & Patarroyo, ), Pv GAMA (Baquero et al, ), and EBP2 (Ntumngia et al, ), whereas Pv DBPRII bound to both RBC and normocytes (Figure c).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…When Pv RON4 binding to RBC ( m = 34 ± 2.7) was compared with binding to normocytes ( m = 11 ± 1.4), it was observed that the amount of rosettes compared with normocytes became significantly reduced, t test: t (10) = 18.68, p = .001 (Figure b,c). This suggested that Pv RON4 binding to RBC depends on a more immature RBC population, similar to that reported for other P. vivax antigens, such as Pv AMA1 (Arevalo‐Pinzon, Bermudez, Hernandez, Curtidor, & Patarroyo, ), Pv GAMA (Baquero et al, ), and EBP2 (Ntumngia et al, ), whereas Pv DBPRII bound to both RBC and normocytes (Figure c).…”
Section: Resultssupporting
confidence: 81%
“…All Rosetting assays were performed three times in triplicate PvRON4 binding to RBC (m = 34 ± 2.7) was compared with binding to normocytes (m = 11 ± 1.4), it was observed that the amount of rosettes compared with normocytes became significantly reduced, t test: t(10) = 18.68, p = .001 (Figure 1b,c). This suggested that PvRON4 binding to RBC depends on a more immature RBC population, similar to that reported for other P. vivax antigens, such as PvAMA1 (Arevalo-Pinzon, Bermudez, Hernandez, Curtidor, & Patarroyo, 2017), PvGAMA , and EBP2 (Ntumngia et al, 2016), whereas PvDBPRII bound to both RBC and normocytes (Figure 1c). Several reports have shown that different P. falciparum strains differ regarding their ability to invade RBC treated with different enzymes, such as trypsin, chymotrypsin, and neuraminidase, removing different receptors from RBC surface DeSimone et al, 2009).…”
supporting
confidence: 83%
“…Although the majority of newly identified genes belong to subtelomeric gene families, we confirmed the recently identified EBP2 (erythrocyte binding protein 2, PVP01_0102300) and RBP2e (reticulocyte binding protein 2e, PVP01_0700500) genes 11 . These genes are members of families encoding proteins implicated in host cell recognition during red blood cell (RBC) invasion, and present potential vaccine targets 4851 .…”
Section: Dataset Validationmentioning
confidence: 99%
“…This serves as a strong argument for the existence of only one invasion pathway for P. vivax . However, in the recent years, many studies have reported P. vivax infections in Duffy-negative patients (220, 222–228), suggesting that P. vivax merozoites may use another pathway to invade reticulocytes (229). This may limit the efficacy of vaccine based on the Duffy-binding protein, the ligand of the Duffy antigen (230), by selecting for parasites that are able to invade via this alternative pathway.…”
Section: Redundant Pathways Of Red Blood Cell Invasionmentioning
confidence: 99%